AIDS and the social sciences : common threads - Ulack, Richard, 1942-2011; Skinner, William Francis (University Press of Kentucky, 1991)
Though more than 150,000 AIDS-related deaths have been reported worldwide and between 5 and 10 million people are now infected with its precursor, HIV-1, the deadly and relatively new AIDS virus is still a mystery. AIDS and the Social Sciences: Common Threads, an enlightening examination of the AIDS epidemic from the viewpoints of various social sciences, provides us with clues to that mystery. The essays' original research and firsthand accounts from social scientists offer an excellent overview of the research agendas and directions for a disease that is an increasing presence in our society.